Multistability of bursting rhythms in a half-center oscillator and the protective effects of synaptic inhibition - Ellingson, Parker J.; Shams, Yousif O.; Parker, Jessica R.; Calabrese, Ronald L.; Cymbalyuk, Gennady S. (Frontiers in Cellular Neuroscience, 2024)
For animals to meet environmental challenges, the activity patterns of specialized oscillatory neural circuits, central pattern generators (CPGs), controlling rhythmic movements like breathing and locomotion, are adjusted by neuromodulation. As a representative example, the leech heartbeat is controlled by a CPG driven by two pairs of mutually inhibitory interneurons, heart interneuron (HN) half-center oscillators (HCO). Experiments and modeling indicate that neuromodulation of HCO navigates this CPG between dysfunctional regimes by employing a co-regulating inverted relation; reducing Na + /K + pump current and increasing hyperpolarization-activated (h-) current. Simply reducing pump activity or increasing h-current leads to either seizure-like bursting or an asymmetric bursting dysfunctional regime, respectively.Here, we demonstrate through modeling that, alongside this coregulation path, a new bursting regime emerges. Both regimes fulfill the criteria for functional bursting activity. Although the cycle periods and burst durations of these patterns are roughly the same, the new one exhibits an intra-burst spike frequency that is twice as high as the other. This finding suggests that neuromodulation could introduce additional functional regimes with higher spike frequency, and thus more effective synaptic transmission to motor neurons. We found that this new regime co-exists with the original bursting. The HCO can be switched between them by a short pulse of excitatory or inhibitory conductance. In this domain of coexisting functional patterns, an isolated cell model exhibits only one regime, a severely dysfunctional plateau-containing, seizure-like activity. This aligns with widely reported notion that deficiency of inhibition can cause seizures and other dysfunctional neural activities. We show that along the coregulation path of neuromodulation, the high excitability of the single HNs induced by myomodulin is harnessed by mutually inhibitory synaptic interactions of the HCO into the functional bursting pattern.